2007
DOI: 10.1111/j.1744-7909.2007.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Signal Transduction in Rice

Abstract: In the past decade, significant knowledge has accumulated regarding gibberellin (GA) signal transduction in rice as a result of studies using multiple approaches, particularly molecular genetics. The present review highlights the recent developments in the identification of GA signaling pathway components, the discovery of GA-induced destruction of GA signaling repressor (DELLA protein), and the possible mechanism underlying the regulation of GAresponsive gene expression in rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The expression level of miR159 has been shown increased by abscisic acid (ABA), a plant hormone involved in bud and seed dormancy, root growth, leaf senescence and abscission, stomata opening and stress protection [ 191 ]. Besides, miR159, miR319 and miR166 have been proven to be involved in the plant hormone gibberellin pathway [ 192 194 ]. Hormone modulation of miRNAs in plant has been exemplified in the case of auxin.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of miR159 has been shown increased by abscisic acid (ABA), a plant hormone involved in bud and seed dormancy, root growth, leaf senescence and abscission, stomata opening and stress protection [ 191 ]. Besides, miR159, miR319 and miR166 have been proven to be involved in the plant hormone gibberellin pathway [ 192 194 ]. Hormone modulation of miRNAs in plant has been exemplified in the case of auxin.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, key genes in the GA synthesis pathway are mutated, and low levels of GA content cause dwarfing (Sakamoto et al., 2004; Spielmeyer et al., 2002); on the other hand, gibberellin metabolic defects can also cause plant dwarfing, mainly in the study of DELLA proteins (Hirano et al., 2012; Sun, 2011; Zhang et al., 2014), F‐box proteins (Sasaki et al., 2003), Sleepy1 (SLY1) (McGinnis et al., 2003), and the Gibberellin receptor GID1 (Ueguchi‐Tanaka & Matsuoka, 2010). In general, GA binds to GID1 and DELLA proteins to form a GA‐GID1‐DELLA protein complex, promotes F‐box ubiquitination in the DELLA protein and SCF complex, alleviates the inhibition of DELLA protein, and activates downstream‐related genes (Colebrook et al., 2014; Fan et al., 2007; Sun, 2010). Most of previous studies have identified these key factors using GA‐insensitive mutants, especially gid1 in rice (Ueguchi‐Tanaka et al., 2005), gai (Peng et al., 1997), rga (Silverstone et al., 1998), dwarf mutants gid2 , and sly1 in Arabidopsis (McGinnis et al., 2003; Sasaki et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mutants deficient in GA biosynthesis or impaired in GA signaling exhibit a dwarfed plant phenotype. In model plants like dicotyledon Arabidopsis and monocotyledon rice, several genes that encode the GA receptor GA-INSENSITIVE DWARF1 (GID1), DELLA proteins, and the F-box proteins GA-INSENSITIVE DWARF2 (GID2) and AtSLEEPY1 (AtSLY1) have been identified by screening GA signaling mutants (Peng et al 1997;Silverstone et al 1998;Ikeda et al 2001;Itoh et al 2002;McGinnis et al 2003;Sasaki et al 2003;Gomi et al 2004;Ueguchi-Tanaka et al 2005, 2007, an integral picture of the GA signal transduction pathway has started to emerge (Eckardt 2007;Fan et al 2007;Jiang and Fu 2007;Davière et al 2008;Hirano et al 2008;Schwechheimer 2008). Nuclear-localized DELLA proteins are GA signaling repressors that restrain gene expression associated with GA-induced growth processes (Eckardt 2007;Schwechheimer 2008).…”
Section: Introductionmentioning
confidence: 99%